2017
DOI: 10.1007/s12602-017-9351-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Probiotics on Halitosis: a Systematic Review and Meta-analysis

Abstract: Although several studies have evaluated the inhibitory effect of probiotics on halitosis, findings are inconsistent. This systematic review and meta-analysis of randomized clinical trials (RCT) was conducted to summarize the evidence on the effect of probiotics on halitosis. RCT on any type of probiotic treatment with at least 2-week duration were identified through electronic databases (PubMed, EMBASE, Web of Science, and the Cochrane Central Register of Controlled Trials) and hand searched between 1946 and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…38 Os autores dessa pesquisa concluíram que o uso do probiótico com S. salivarius foi eficiente para diminuir os índices de halitose, contudo, deve -se analisar que o fator tempo é considerativo para sanar o problema, além de que mais estudos devem ser feitos para elucidar de facto a eficácia do tratamento com probióticos, tendo em vista que os achados são quantitativa e qualitativamente insuficientes para recomendações adicionais, especialmente no que diz respeito às estratégias de administração. 39 Com base nas evidências, o tratamento mais rápido e eficaz para a halitose, quando referente ao mau odor matinal, é a escovagem da língua associada ao uso de pastas dentífricas contendo derivados do zinco ou o enxaguar da boca com 15 ml de água, e com efeito similar beber um copo de 200 ml de água ao amanhecer. 23,30 Por conseguinte, é salutar verificar o motivo da queixa principal do paciente e averiguar se essas intervenções podem se aplicar.…”
Section: Discussionunclassified
“…38 Os autores dessa pesquisa concluíram que o uso do probiótico com S. salivarius foi eficiente para diminuir os índices de halitose, contudo, deve -se analisar que o fator tempo é considerativo para sanar o problema, além de que mais estudos devem ser feitos para elucidar de facto a eficácia do tratamento com probióticos, tendo em vista que os achados são quantitativa e qualitativamente insuficientes para recomendações adicionais, especialmente no que diz respeito às estratégias de administração. 39 Com base nas evidências, o tratamento mais rápido e eficaz para a halitose, quando referente ao mau odor matinal, é a escovagem da língua associada ao uso de pastas dentífricas contendo derivados do zinco ou o enxaguar da boca com 15 ml de água, e com efeito similar beber um copo de 200 ml de água ao amanhecer. 23,30 Por conseguinte, é salutar verificar o motivo da queixa principal do paciente e averiguar se essas intervenções podem se aplicar.…”
Section: Discussionunclassified
“…[33][34][35][36][37] However, a previous systematic review showed that probiotic therapy for halitosis is associated with insufficient evidence for it to be recommended. 38 Thus, it is necessary to carry out a focused analysis of the therapeutic effects of probiotics in the treatment of halitosis.…”
Section: Open Accessmentioning
confidence: 99%
“…[1][2][3] Probiotics usage in Dentistry is gaining pace as there is an increase in the number of studies presenting favourable outcomes. Probiotics ingestion has numerous oral health benefits such as improvement of outcomes after nonsurgical periodontal therapy, 4 breduction of clinical gingivitis, 5,6 halitosis, 7 reduction in the severity of cancer therapy-induced oral mucositis, 8 reduction of oral candidiasis in denture wearers, 9 reduction of S.mutans counts. 10 Periodontal benefits of consumption of probiotics might be because probiotics will reduce the load of harmful bacteria, reduce the adhesion and proliferation of bacteria on the tooth surface, inhibition of intercellular plaque matrix formation, reduction of toxins produced thereby decreasing the plaque formation and gingivitis.…”
Section: Introductionmentioning
confidence: 99%